Southern Thailand’s Lessons: Policy Tools for Health Security - Jeawkok, Jirachaya; Morsu, Syuwari; Sukmak, Phen; Choosuk, Chanisada; Kwiecien, Kanyarat; Saengtong, Thanidaphat (Ratchaphruek Journal, 2026)
This study aimed to extract lessons from the project developing systems and mechanisms to support public health policies for health promotion in Southern Thailand, with a focus on health security. Employing qualitative research methods, data were collected from 12 stakeholders through in-depth interviews and focus group discussions. The research instruments included semi-structured interview guides and focus group protocols, Data were analyzed using content analysis. The results found that: 1) Systematic and participatory project management proved highly effective, successfully fostering collaboration in wellness tourism and facilitating the implementation of multicultural health service standards in pilot hospitals. 2) Community involvement and the application of cultural knowledge were identified as critical success factors, while a lack of inter-agency integration and communication challenges were the main obstacles. 3) The study confirms Phuket's strong potential to evolve into a regional multicultural health and wellness hub, with insights into Muslim-friendly services and local culture being vital for designing appropriate health policies; and 4) future development should emphasize strengthening network collaboration, integrating economic, social, and cultural dimensions into service design, and establishing continuous monitoring and evaluation to support participatory health policy implementation for sustainable development of the Southern health system.